Relation between exponential and gamma distribution [duplicate]

This question already has an answer here:

If T and S are distributed exponential T,S = Exp(lambda). What is distribution T+S? The solutions says its gamma(2,lambda), but I don't understand why. I can only guess the answer by knowing that E(X+Y) = E(X)+E(Y) and in this case its 1/lambda+1/lambda = 2/lambda. And we know E from gamma distribution that is n/lambda, so T+S is gamma distribution with parameters 2 and lambda. I would also like to ask what in gamma distribution means gamma(n )

marked as duplicate by heropup probability StackExchange.ready(function() { if (StackExchange.options.isMobile) return; $('.dupe-hammer-message-hover:not(.hover-bound)').each(function() { var$hover = $(this).addClass('hover-bound'),$msg = $hover.siblings('.dupe-hammer-message');$hover.hover( function() { $hover.showInfoMessage('', { messageElement:$msg.clone().show(), transient: false, position: { my: 'bottom left', at: 'top center', offsetTop: -7 }, dismissable: false, relativeToBody: true }); }, function() { StackExchange.helpers.removeMessages(); } ); }); }); Dec 17 '17 at 8:14

Proving two distributions are equivalent requires more than proving the first few moments are equal.

We know the MGF (moment generating function) of the Gamma($\alpha$,$\beta$) distribution is:

$$M_X(t)=(1-t/\beta)^{-\alpha}$$

Now take two independent exponential random variables $Y$ and $Z$:

$$Y,Z\sim \text{Exp}(\lambda)$$

Now:

\begin{align}M_{Y+Z}(t)&=M_Y(t) M_Z(t)\\ &=\frac{\lambda^2}{(\lambda-t)^2} \end{align}

The above expression is the MGF of the Gamma parameterized as follows:

$$Y+Z\sim \text{Gamma}(2,\lambda)$$

What you have circled in red is the Gamma function. It is defined as:

$$\Gamma(z)=\int_{0}^{\infty}x^{z-1}e^{-x}\,dx$$